Between Legality and Justice: A Critical Study of the Supreme Court’s Judicial Reasoning in Dispute of the Awyu Customary Forest - Achmad Hariri; A. Basuki Babussalam; Muhammad Aunurrochim Mas’ad Saleh (Jurnal Jurisprudence, 2025)
ABSTRACT Purpose of the Study: This research aims to analyze the application of legal positivism and living law approaches in judicial reasoning, particularly in the decisions of the Jayapura Administrative Court No. 6/G/LH/2023/PTUN.JPR, the Manado High Administrative Court No. 92/B/LH/2023/PT.TUN.MDO, and the Supreme Court Decision No. 458 K/TUN/LH/2024. In addition, this study evaluates the extent to which the principles of substantive justice and the protection of customary communities are accommodated in Indonesia’s judicial practice. Methodology: This study employed a normative legal research method using three main approaches: the statutory approach, the case approach, and the conceptual approach. The case approach was used to profoundly analyze three judicial decisions involving the Awyu indigenous people, namely the Jayapura Administrative Court Decision No. 6/G/LH/2023/PTUN.JPR, the Manado High Administrative Court Decision No. 92/B/LH/2023/PT.TUN.MDO, and the Supreme Court Decision No. 458 K/TUN/LH/2024. The conceptual approach linked the theories of legal positivism, living law, and substantive justice. Results: The findings indicate a dominance of formal legality and legal positivism in the judicial reasoning at both the appellate and cassation levels. The Supreme Court rejected the lawsuit of the Awyu indigenous people on the grounds of expiration, as it exceeded the 90-day filing period, without addressing the substantive issues of violations of environmental and indigenous rights. This formal-positivistic pattern of judgment creates a judicial barrier that hinders customary communities’ access to justice and disregards living law. Applications of this Study: This study contributes scientifically to strengthening the discourse on legal pluralism and developing a paradigm of substantive justice within Indonesia’s legal system. It emphasizes the importance of integrating customary legal values and ecological justice into judicial processes. Novelty/Originality of this Study: The novelty of this research lies in its critical and comparative analysis of judicial reasoning across three levels of adjudication in the Awyu case, including the examination of dissenting opinions at the Supreme Court level. It reveals the historical tension between positive law and the substantive justice values of indigenous peoples, highlighting the urgency of reconstructing the judicial paradigm. Keywords: Judicial Decision; Legal Positivism; Substantive Justice; Indigenous People; Awyu Tribe.   ABSTRAK Tujuan Penelitian: Penelitian ini bertujuan untuk menganalisis penerapan pendekatan positivisme hukum dan living law dalam pertimbangan hakim, khususnya pada Putusan PTUN Jayapura No. 6/G/LH/2023/PTUN.JPR, Putusan PT.TUN Manado No. 92/B/LH/2023/PT.TUN.MDO, dan Putusan Mahkamah Agung No. 458 K/TUN/LH/2024. Selain itu, penelitian ini menilai sejauh mana prinsip keadilan substantif dan perlindungan terhadap Masyarakat Hukum Adat (MHA) diakomodasi dalam praktik peradilan Indonesia. Metodologi: Penelitian ini menggunakan metode hukum normatif dengan tiga pendekatan utama: pendekatan perundang-undangan, pendekatan kasus, dan pendekatan konseptual. Pendekatan kasus digunakan untuk menganalisis secara mendalam tiga putusan pengadilan dalam sengketa Suku Awyu, yaitu Putusan PTUN Jayapura No. 6/G/LH/2023/PTUN.JPR, Putusan PT.TUN Manado No. 92/B/LH/2023/PT.TUN.MDO, dan Putusan Mahkamah Agung No. 458 K/TUN/LH/2024. Pendekatan konseptual mengaitkan teori hukum positivistik, living law, dan keadilan substantif. Hasil: Hasil penelitian menunjukkan adanya dominasi pendekatan legalitas formal dan positivisme hukum dalam praktik peradilan tingkat banding dan kasasi. Putusan MA menolak gugatan MHA Suku Awyu berdasarkan alasan kedaluwarsa karena melampaui batas waktu 90 hari, tanpa menyentuh substansi pelanggaran lingkungan dan hak adat. Pola putusan formil-positivistik ini menciptakan judicial barrier yang menghambat akses MHA terhadap keadilan dan mengabaikan living law. Aplikasi Penelitian: Penelitian ini bermanfaat sebagai kontribusi ilmiah untuk penguatan wacana pluralisme hukum dan pengembangan paradigma keadilan substantif dalam sistem hukum Indonesia. Studi ini menekankan pentingnya integrasi nilai-nilai hukum adat dan keadilan ekologis ke dalam proses peradilan. Kebaruan: Kebaruan studi ini terletak pada analisis kritis dan komparatif terhadap pola pertimbangan hakim pada tiga tingkat peradilan kasus Suku Awyu, termasuk menguji argumen dissenting opinion di tingkat MA, untuk mengungkap ketegangan historis antara hukum positif dan nilai-nilai keadilan substantif MHA, serta urgensi rekonstruksi paradigma peradilan. Kata Kunci; Putusan Hakim; Positivisme Hukum, Keadilan Substantif; Masyarakat Hukum Adat; Suku Awyu